Interview with Javier Dario Restrepo:"In journalism, the end does not justify the means" - Herrera Damas, Susana (2022)
The fifty years in which he has been a journalist have not discouraged him from unconditionally defending journalistic ethics. In this interview, Colombian Javier Darío Restrepo refers to the crisis which nowadays affects journalism, to the place of ethics in the editing rooms and to the viability of self regulation in Latin American media. Deeply convinced that ethics sell, Restrepo states that, in journalism, as in any other human activity, the end never justifies the means.